Jasmine girl at haji ali and other strories - Sarangi, Mrutyunjay (Bhubneswar Nayapalli, 2022)
The book is about piano, the girl in red, monkey dance, a walk in lodhi gardens, Jasmine girl at Haji ali.
Keywords: Stories